Detection of Water Quality for Health Monitoring through CNN Image Analysis - Gour, Ayush Roy; Kumar, Revanth; Reddy, Vidhit; Amruthaluru, Uma Datta; Hariharan, Shanmugasundaram; Kukreja, Vinay (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
This work offers an effective method for finding water features using netting stimulated by a convolutional neural network (CNN) countenance research. Conventional techniques for assessing the condition of the water may be difficult and time-consuming. The proposed methodology seeks to expedite this procedure by utilizing CNNs' proficiency in concept recognition tasks, which automates and enhances the accuracy of water quality assessment. Data collection, preprocessing, CNN construction, model preparation, and deployment inside a reliable netting application are among the techniques used. This research work establishes the effectiveness of CNN-located methodologies in natural resource protection by a study survey. Building on this support, the proposed technique offers a flexible and convincing real-occasion water status assessment solution. The outcomes of the experiments demonstrate how well the proposed CNN model performs when it comes to correctly classifying water-type limitations from pictures. This strategy makes responsible and convenient use of natural resources possible while also providing significant advantages for community health and preservation.